Antibodies to Antigenic Site A of Influenza H7 Hemagglutinin Provide Protection against H7N9 Challenge - Schmeisser, Falko (PLoS One, 2015)
Identifying major antigenic and protective epitopes of the H7 hemagglutinin (HA) will be important for understanding the antibody response to vaccines developed against the novel influenza H7N9 viruses that emerged in China in 2013. To facilitate antigenic characterization of the H7N9 HA and to develop reagents for evaluation of H7N9 candidate vaccines, we generated a panel of murine monoclonal antibodies (mAbs) to the HA of A/Shanghai/2/2013 using mammalian cell-derived virus-like particles (VLP) containing the H7 HA. Neutralizing antibodies identified an HA epitope corresponding to antigenic site A on the structurally similar influenza H3 hemagglutinin. Importantly, the neutralizing antibodies protect against A/Shanghai/2/2013 challenge. This antigenic site is conserved among many H7 viruses, including strains of both Eurasian and North American lineage, and the isolated neutralizing antibodies are cross-reactive with older H7 vaccine strains. The results indicate that the identified antigenic site is a potentially important protective epitope and suggest the potential benefit of cross-reactive antibody responses to vaccination with H7 candidate vaccines.